2014
DOI: 10.1093/scan/nsu077
|View full text |Cite
|
Sign up to set email alerts
|

Out of control: Evidence for anterior insula involvement in motor impulsivity and reactive aggression

Abstract: Inhibiting impulsive reactions while still defending one's vital resources is paramount to functional self-control and successful development in a social environment. However, this ability of successfully inhibiting, and thus controlling one's impulsivity, often fails, leading to consequences ranging from motor impulsivity to aggressive reactions following provocation. Although inhibitory failure represents the underlying mechanism, the neurocognition of social aggression and motor response inhibition have tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 43 publications
4
95
2
1
Order By: Relevance
“…Second, activity in the CMS regions significantly moderates activity in other brain regions associated with moral emotion and motivation (e.g., midbrain including the ventral tegmental area, ventral striatum, insula, OFC [57][58][59][60][61]) while subjects are solving moral problems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, activity in the CMS regions significantly moderates activity in other brain regions associated with moral emotion and motivation (e.g., midbrain including the ventral tegmental area, ventral striatum, insula, OFC [57][58][59][60][61]) while subjects are solving moral problems.…”
mentioning
confidence: 99%
“…First, previous experiments have demonstrated that the PI is the core of the immediate processing of affective responses and the induction of subjective feelings [73,74], particularly negative emotions (e.g., pain and disgust) [73][74][75][76][77], that play fundamental roles in moral cognition [42,53]. Moreover, the AI is closely associated with the integration of cognition and emotion [78][79][80][81][82], conscious and interceptive awareness, monitoring of aroused emotional responses [28,83,84], and finally, the modulation of motivational force [60,61,85]. Given these previous works, the present study chooses the AI and PI as the regions of interest for the GCA.…”
mentioning
confidence: 99%
“…This activation was apparent in the overall contrast anti‐cues versus pro‐cues (Figure 4), and mirrored in the contrast map of anti‐cue trials with short cue‐target interval compared to pro‐cue trials with short cue‐target interval (Figure 6). Anterior insular activation has repeatedly been associated with response restraint and response cancellation (Dambacher et al., 2014a, 2014b, 2014c; Swick et al., 2011). It should be emphasized that the reported insular activation extended very prominently into the inferior frontal cortex, which is classically associated with motor response inhibition (Aron, Robbins, & Poldrack, 2004; Chambers et al., 2006, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This contrast also yielded more activity in right superior frontal gyrus during the short‐interval trials. This region was shown to be a core region involved in successful response inhibition and specifically action restraint (Aron et al., 2004; Dambacher et al., 2014a, 2014b; Swick et al., 2011). Research using noninvasive brain stimulation further emphasized the role of the right superior frontal gyrus in response restraint (Dambacher et al., 2014c).…”
Section: Discussionmentioning
confidence: 99%
“…The insula has been implicated in different modalities of self-control (Dambacher et al, 2014) and decision-making with risk-taking (Paulus et al, 2003;Xue et al, 2010), suggesting it plays a role in drug addiction (Naqvi et al, 2014). However, previous studies have shown mixed results as to whether drug addiction was associated with increased or decreased gray matter volume in the insula.…”
Section: Right Insula Volume In Meth Usersmentioning
confidence: 99%